The Application of the Mobile Learning Game “Duschans Schulweg” as the Vocabulary Training for the Topic “Schule” in the Class 10 of the Main Course at SMA Negeri I Malang - Dyah Jasmine Mayangsari (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
The Purposes of this research are to describe the process when the students playa game called Duschans Schulweg and to know their reaction after playing the game. The participants of this Research are students of German lesson class, at SMA Negeri I Malang who have problems with German vocabularies learning because they only receive German lesson once a week. It makes them poor in vocabularies. The teacher must use a suitable media in German lesson so that the students don’t have any difficulties in vocabulary learning.This research uses qualitative-descriptive research method. The subjects of this research are 32 students of German class, grade 10 at SMA Negeri I Malang and their German learning activities. The data of this research are the process of learning German using Duschans Schulweg and the students reaction after playing the game. The instruments of this research are questionnaires and observation sheets.The result of this research shows that the game Duschans Schulweg is a suitable media to learn vocabularies easily. This research gained positive responses from the students, it makesthem motivated and they say they can learn German vocabularies quickly.